2000
DOI: 10.1017/s0266467400001681
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal pollination of Parkia velutina by Megalopta bees in Amazonia and its possible significance in the evolution of chiropterophily

Abstract: Canopy observations of the rain forest tree Parkia velutina (Leguminosae: Mimosoideae) in Amazonian Brazil indicate that it is pollinated by night-flying bees. The small red flowers are organized into spherical heads; they open in the late afternoon and attract Megalopta bees (Halictidae: Augochlorini) which forage for pollen after dark. In contrast to the numerous bat-pollinated species of Parkia, no nectar was detected. Nocturnal melittophily is proposed as a possible intermediate stage in the evolution of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 18 publications
0
39
0
2
Order By: Relevance
“…Females forage on flowers to collect nectar and pollen, which is necessary for larval development. In Mexico and Panama, Megalopta uses many plant species for pollen (Gonzalez et al 2010a;Tierney et al 2012), which have both diurnal and nocturnal anthesis (Falcão et al 1992;Ervik & Feil 1997;Hopkins et al 2000;Gressler et al 2006;Oliveira et al 2009), during either the dry or wet season (Wcislo et al 2004). Given the similar seasonal pattern of Megalopta observed in this study in comparison with that recorded in Central America (Wolda & Roubik 1986), we assume that the attractiveness of bait traps might be related to the fragrance produced by the flowers that produce nectar, pollen or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Females forage on flowers to collect nectar and pollen, which is necessary for larval development. In Mexico and Panama, Megalopta uses many plant species for pollen (Gonzalez et al 2010a;Tierney et al 2012), which have both diurnal and nocturnal anthesis (Falcão et al 1992;Ervik & Feil 1997;Hopkins et al 2000;Gressler et al 2006;Oliveira et al 2009), during either the dry or wet season (Wcislo et al 2004). Given the similar seasonal pattern of Megalopta observed in this study in comparison with that recorded in Central America (Wolda & Roubik 1986), we assume that the attractiveness of bait traps might be related to the fragrance produced by the flowers that produce nectar, pollen or both.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that only females have been captured in the orchid bee baits suggests that they use olfactory clues to search for pollen during dim-light conditions. Some species of plants used by dim light bees that also produce scents are Prestoea schultzeana (Arecaceae), Parkia velutina (Fabaceae), and Ternstroemia dentata (Theaceae) (Ervik & Feil 1997;Melo 1995;Hopkins et al 2000). If this is correct, the olfactory system may have also played as important a role in the evolution of Megalopta as the visual system (Greiner et al , 2005Kelber et al 2005;Warrant 2004).…”
Section: Discussionmentioning
confidence: 99%
“…1). Although our current knowledge about nocturnal bees is limited, M. genalis has been well studied, and we know a good deal about its nest structure (Sakagami 1964;Janzen 1968) and biology (Wolda and Roubik 1986;Roulston 1997;Hopkins et al 2000;Arneson and Wcislo 2003;Smith et al 2003). Behavioural studies have shown that M. genalis females are only active 1 h before dawn and 20 min after dusk when light intensities under the dense forest canopy are equivalent to starlight intensities above the canopy (Almut Kelber, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Megalopta bees use more than 60 angiosperm species at one site in central Panama (I. Lopez, A. R. Smith & W. Wcislo 2007, unpublished data), but little is known of their role as potential pollinators. Hopkins et al [64] noted that Megalopta was the most abundant visitor to Parkia velutina in Brazil, and hypothesized that nocturnal bees may have played a role in opening a new niche (night-blooming flowers), which was subsequently exploited by bats (for a more detailed discussion, see [17]). …”
Section: Discussion (A) Opsin Evolutionmentioning
confidence: 99%